Punjab, Punjabi Culture and Civilization in Dr. Muhammad Hanif Chaudhary's Columns (An Overview) - Hassan, Sadia; Latif, Wasif; Bukhari, Syed Ghazanfar Hussain (sourcecoder, 2023)
The man who is like a hundred years old institutions in his personality; a walking encyclopedia of art, culture and literature of Punjab. Dr. Muhammad Hanif Chaudhary is a renowned journalist writer and researcher of Southern Punjab. Research, poetry, novel, drama, travelogue and short stories are some prominent genres of his writings. His life story and creative work inspire every reader. The Punjab government granted him the “Pride of Punjab Award” to admire and appreciate his literary work. He is also known in foreign Punjabi circles in Canada and India. He is the only living Punjabi writer of this age whose work is honoured to be an academic research subject at M.Phil. and Ph.D. levels in different Universities in Pakistan. Dr. Muhammad Hanif Chaudhary has a strong bond and great affection for the soil of Punjab, its people and its culture & civilization. His writings especially his columns that were published in different newspapers are evidence of his keen observations and sensitive heart regarding changes in different social and cultural traditions of his age. This article discovers the writer’s source of inspiration for the cultural and civilizational changes of his age in Punjab through the selected topics in his published columns.